Creativity, Society, and the Role of Socially Engaged Art in Higher Arts Education - Lehikoinen, Kai (Routledge Research in Arts Education, 2025)
This interdisciplinary book explores socially engaged art as a subject of study and its relevance in higher arts education institutions' third mission—giving back to society and engaging with the community—to build a sustainable higher arts education for the future. Drawing on data from two large-scale EU-funded projects—supplemented by interviews, educational document analysis, and secondary data—this book explores emerging trends in the arts sector and the role of arts universities in cross-sector collaboration, innovation, and actions towards social and environmental responsibility. Chapters posit theoretical analysis, case studies and practically orientated examples from countries including the United States, Ghana, Indonesia, and from across Europe to explore the growing demands for the positive societal impact of higher arts education. Located at the interface between the sociology of higher arts education and community engagement, the book explores a richness of international contexts including activism, churches, refugee work, eldercare, gender politics, prisons and many others. This timely volume responds to the urgent need to investigate the full potential of socially engaged art in higher arts education. As such, it will appeal foremost to scholars, researchers, postgraduate students, and teachers in higher arts education and the sociology of education. Practitioners working in arts curriculum design, university-society partnerships, and those focused on creating inclusive and respectful spaces in higher arts education and research, will also find the volume of use.